Genotype specificity among hosts, pathogens, and beneficial microbes influences the strength of symbiont-mediated protection - Parker, Benjamin J; Hrček, Jan; McLean, Ailsa H C; Godfray, H Charles J (Evolution; international journal of organic evolution, 2017)
The microbial symbionts of eukaryotes influence disease resistance in many host-parasite systems. Symbionts show substantial variation in both genotype and phenotype, but it is unclear how natural selection maintains this variation. It is also unknown whether variable symbiont genotypes show specificity with the genotypes of hosts or parasites in natural populations. Genotype by genotype interactions are a necessary condition for coevolution between interacting species. Uncovering the patterns of genetic specificity among hosts, symbionts, and parasites is therefore critical for determining the role that symbionts play in host-parasite coevolution. Here, we show that the strength of protection conferred against a fungal pathogen by a vertically transmitted symbiont of an aphid is influenced by both host-symbiont and symbiont-pathogen genotype by genotype interactions. Further, we show that certain symbiont phylogenetic clades have evolved to provide stronger protection against particular pathogen genotypes. However, we found no evidence of reciprocal adaptation of co-occurring host and symbiont lineages. Our results suggest that genetic variation among symbiont strains may be maintained by antagonistic coevolution with their host and/or their host's parasites.
Keywords: symbióza; mutualism; Fungi; genetická variace; Genotype; fylogeneze; Phylogeny; Coevolution; endosymbiont; houby; mšice; symbiont-mediated resistance; fungal pathogens; Animals; zvířata; pea aphid (Acyrthosiphon pisum); genotyp; Aphids; Symbiosis; Genetic Variation